STRATEGI PENGEMBANGAN KOPERASI DI ERA DIGITAL - Adik Ayu; Ahmad Gianto; Neza Aini Ariyanto; Nurus Sobakh (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The rapid development of digital technology has changed the paradigm of the global economy and encouraged cooperatives to adapt in order to remain relevant and competitive. This article aims to formulate cooperative development strategies in the digital era through a technology-based transformation approach using qualitative methods through literature studies. The study results show that cooperative digitalization is a necessity to increase the efficiency, effectiveness, and transparency of the organization (Untoro et al., 2024, Parta: Jurnal Pengabdian Kepada Masyarakat, 4(2), 121–133). In addition, the priority of development strategy lies in the utilization of technology and innovation so that cooperatives can compete with digital-based businesses (Pradana & Husaein, 2023, Jurnal Ilmiah Media Sisfo, 17(1), 106–115). Digital transformation also requires strengthening organizational governance and technology-based internal control systems to minimize the risk of fraud (Mulyaningtyas & Wardana, 2025, Jurnal Ilmiah Akuntansi Indonesia, 10(2)). Thus, the development of cooperatives in the digital era requires the integration of technology utilization, improvement of “human resource (HR)” quality, and the implementation of good governance principles to support the sustainability of cooperatives